The Influence of Age, Working Hours, and Use of Personal Protective Equipment on the Risk of Work Accidents: A Case Study at the TKBM Cooperative Work Groups 1 and 2, Sorong Port - Nur Jannah; Rais Dera Pua Rawi; Akmal Ridwan (IECON: International Economics and Business Conference, 2025)
This study aims to examine the influence of age, working hours, and the use of personal protective equipment (PPE) on the risk of occupational accidents among port workers, particularly in Work Groups 1 and 2 of the TKBM Cooperative at Sorong Port, Indonesia. Given the high number of reported accidents 40 cases in the last two years. This study highlights a critical safety issue in the maritime logistics sector. A quantitative approach with a descriptive method was employed. Data were collected from 50 dockworkers through a closed-ended Likert-scale questionnaire and direct observation. The analysis was conducted using multiple linear regression with SPSS version 27. The results indicated that age (p = 0.085) and working hours (p = 0.340) did not have a significant effect on the risk of work accidents when considered individually. In contrast, PPE usage showed a significant impact (p = 0.008), and all three variables together had a statistically significant combined effect (p = 0.001). These findings underscore the importance of consistent PPE usage in preventing occupational accidents and suggest that integrated safety management strategies should be prioritized, especially in physically demanding work environments such as ports. This study contributes to the occupational health and safety literature by addressing a research gap in high-risk labor sectors and offers practical insights for improving policy and training programs in port labor management.